Experimental study of heat transfer augmentation in non-circular duct using combined nanofluids and vortex generator - Ahmed H.E.; Ahmed M.I.; Yusoff M.Z.; Hawlader M.N.A.; Al-Ani H. (Elsevier Ltd, 2023)
Aluminum; Ducts; Friction; Heat transfer; Reynolds number; Vortex flow; Vorticity; Distilled water; Friction factors; Heat transfer and friction factors; Heat transfer augmentation; Nanofluids; Noncircular ducts; Two particles; Vortex generators; Nanofluidics